Comparison of patient-reported outcomes among different types of oncoplastic breast surgery procedures. Issue 9 (September 2022) - Ritter, Mathilde; Oberhauser, Ida; Montagna, Giacomo; Zehnpfennig, Lea; Schaefer, Kristin; Ling, Barbara M.; Levy, Jeremy; Soysal, Savas D.; Müller, Madleina; López, Liliana Castrezana; Schwab, Fabienne D.; Kurzeder, Christian; et al.
Summary: Background: This study aims to compare patient-reported outcomes (PROs) after different types of oncoplastic surgery (OPS) procedures and correlate the results with previously published normative data from women with no prior history of breast cancer (BC) and breast surgery. Methods: Cross-sectional study of patients with stage I-II BC undergoing a specific selection of OPS procedures from 04/2012 to 12/2018 by three breast surgeons at a single tertiary referral hospital in Switzerland. PROs were evaluated using the postoperative BREAST-Q questionnaire. Results: One hundred twenty-seven patients met the inclusion criteria and were surveyed. All OPS techniques achieved comparably elevated scores in satisfaction with breasts, psychosocial, and sexual well-being. Compared to normative data of healthy women, all OPS groups postoperatively achieved significantly better satisfaction with breasts, psychosocial, and sexual well-being. Conclusion: This study shows high PROs across all types of OPS, which were superior to normative data from healthy women. Our findings confirm that OPS is associated with high quality of life and patient satisfaction.